Sensory Architecture and Public Spaces in the Practice of the Ancestral Ritual of Huaylarsh in the District of Pucara - Unocc Ospina, Christian Raúl (2024)
In this research, we propose to see the incidence of sensory architecture in public spaces in the Peruvian high Andean zone of the district of Pucara, an environment where the ancestral dance known as Huaylarsh is practiced, which has a background with agriculture and pastoral love. From a diagnosis, we will detect the considerations of the relations of the sensorial characters in the urban environment, opening a set of questions in relation to the cultural development in the towns that need diffusion and support in the expression of their most representative customs. The information on local public spaces was collected by means of an observation sheet, in which several general characteristics were recorded, such as typology, state of conservation and use of equipment, in addition to focusing on sensory criteria such as accessibility, visual language, fluidity in the environment, harmony of materials and comfortable acoustics. This information is complemented by surveys of residents who use public spaces to understand and contextualize their perception of urban space. It was determined that the level of influence of sensory architecture in various public spaces of the Huaylarsh event is moderately favorable, due to multiple deficiencies in the areas analyzed that prevent the spectator and dancer from fully enjoying the event.